High‐Sensitivity Cardiac Troponin After Cardiac Stress Test: A Systematic Review and Meta‐Analysis. Issue 6 (19th March 2019) - Samaha, Eslam; Avila, Audrey; Helwani, Mohammad A.; Ben Abdallah, Arbi; Jaffe, Allan S.; Scott, Mitchell G.; Nagele, Peter
Abstract : Background: The recent introduction of high‐sensitivity cardiac troponin (hs‐cTn) assays has allowed clinicians to measure hs‐cTn before and after cardiac stress testing, but the hs‐cTn release pattern and potential utility in identifying inducible myocardial ischemia are unclear. We thus conducted a systematic review and meta‐analysis to improve our understanding of hs‐cTn release associated with exercise and pharmacological stress testing. Methods and Results: Studies published between January 2008 and July 2016 that reported hs‐cTn change values (high‐sensitivity cardiac troponin T [hs‐cTnT] or high‐sensitivity cardiac troponin I [hs‐cTnI]) in relation to cardiac stress testing were searched and reviewed by 2 independent screeners. Primary outcomes were pooled estimates of absolute and relative hs‐cTn changes after cardiac stress test, stratified by the presence of inducible myocardial ischemia. This meta‐analysis included 11 studies (n=2432 patients). After exercise stress testing, hs‐cTnT increased by 0.5 ng/L or 11% (6 studies, n=406) and hs‐cTnI by 2.4 ng/L or 41% (4 studies, n=365) in patients with inducible myocardial ischemia versus hs‐cTnT by 1.1 ng/L or 18% (8 studies, n=629; P =0.29) and hs‐cTnI by 1.8 ng/L or 72% (4 studies, n=831; P =0.61) in patients who did not develop inducible myocardial ischemia. After pharmacological stress test, hs‐cTnT changed by −0.1 ng/L or −0.4% (6 studies, n=251) and hs‐cTnI by 2.4 ng/L or 32% (2 studies, n=108) in patients with inducible myocardial ischemia versus hs‐cTnT by 0.7 ng/L or 11% (5 studies, n=443, P =0.44) and hs‐cTnI by 1.7 ng/L or 38% (2 studies, n=116; P =0.62) in patients who did not develop inducible myocardial ischemia. Conclusions: hs‐cTn rising patterns after exercise and pharmacological stress testing appear inconsistent and comparably small, and do not appear to be correlated with inducible myocardial ischemia.